Awareness level and the factors for adoption of micro mobility services in India - Aditi Shrivastava (International Journal of Advanced Science and Technology, 2020)
There are various modes of transportation available to the people to choose from, and the choice for the mode of transportation is made taking into consideration the cost of the mode of transport, distance to be travelled, geography and weather of the area where the journey takes place. After a significantly high adoption of ride aggregator apps like Ola and Uber, new age startups have focussed on providing with micro mobility services like bicycles and electric scooters for people to cover small distances. Micro mobility is the area where the electric vehicles have shown the highest penetration and with the big companies like Uber backing a micro mobility start-up like Yulu, it clearly indicates that the market size is going to show an increasing trend. This paper focusses on the need of the consumers that these micro mobility startups are targeting, the current practices in these field that are taking place in different parts of the world and its current adoption and usage in India and the possible future developments required in order for the field to grow. Keywords: Bounce, dockless, e-scooters, intermodal, micro mobility, Rapido, VOGO, Yulu